2014
DOI: 10.1007/s10802-014-9895-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self-Injury in Adolescence: Longitudinal Course, Trajectories, and Intrapersonal Predictors

Abstract: Although prevalence rates of nonsuicidal self-injury (NSSI) has been established throughout adolescence, little is known about the progression of NSSI, and consequently, about the risk factors for youth NSSI engagement. This study aimed to describe the overall longitudinal course of NSSI and the latent trajectory classes of NSSI in a population-based sample of adolescents using multi-wave data. Moreover, this study examined whether sex, lifetime history of depression, rumination, and negative attributional sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
111
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 67 publications
20
111
2
12
Order By: Relevance
“…NSSI is comorbid with both externalizing and internalizing disorders, including borderline personality (BPD), substance use, eating disorders, and depression (Nock et al, 2006). Understanding NSSI within its comorbid disorders is essential, as this behavior portends chronic mental illness (Barrocas et al, 2015), increased suicide risk (Dickstein et al, 2015; Klonsky et al, 2013), and lifetime impairment (Glenn and Klonsky, 2013; In-Albon et al, 2013). Identifying neural signatures distinguishing NSSI from comorbid disorders may elucidate unique neural signatures of higher risk trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…NSSI is comorbid with both externalizing and internalizing disorders, including borderline personality (BPD), substance use, eating disorders, and depression (Nock et al, 2006). Understanding NSSI within its comorbid disorders is essential, as this behavior portends chronic mental illness (Barrocas et al, 2015), increased suicide risk (Dickstein et al, 2015; Klonsky et al, 2013), and lifetime impairment (Glenn and Klonsky, 2013; In-Albon et al, 2013). Identifying neural signatures distinguishing NSSI from comorbid disorders may elucidate unique neural signatures of higher risk trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its elevated occurrence in adolescence (e.g., Giletta et al, 2012), NSSI is associated with several psychopathological indicators and increased risk for future suicide (Klonsky, May, & Glenn, 2013). Both the high prevalence of NSSI and its associated consequences in adolescence have been accounted in several studies in different countries (e.g., U.S.A, European countries, China), suggesting that NSSI is a cross-cultural phenomenon (Barrocas, Giletta, Hankin, Prinstein & Abela, 2015;Giletta et al, 2012;Muehlenkamp, Claes, Haventarpe & Plener, 2012). In Portugal, although studies on NSSI are scarce, some have reported similar prevalence rates (e.g., Xavier, Cunha, & PintoGouveia, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, no research has examined the impact of NSSI or risky behavior engagement. Both behaviors tend to be relatively stable and persist among depressed adolescents 24,25 and may be less likely to change in the context of short-term treatment. Further, as NSSI and risky behavior engagement tend to be more overt, these behaviors may act as early warning signs for families and outpatient clinicians to increase the level of care needed for adolescents.…”
mentioning
confidence: 99%